Analysis of the Interaction Between Tourist Arrivals and Vehicle Density in Bali’s Tourism Destinations - Arianty, A.A Ayu Arun Suwi; Semara, I Made Trisna; Darmayanti, Putu Sri (Jurnal Ilmiah Hospitality Management, 2025)
The rapid development of tourism in Bali has led to an increase in both tourist arrivals and vehicle volume, which potentially causes traffic congestion in major tourist destinations. This study aims to analyze the relationship between the number of tourist visits and vehicle density in Bali. The method used is a quantitative approach with secondary data analysis, including statistics on international and domestic tourist arrivals and the number of vehicles over a specific period. Multiple linear regression analysis was applied to identify the relationship patterns between the research variables. The results show that international tourists (X1) and domestic tourists (X2) simultaneously have a significant effect on the number of vehicles in Bali. The coefficient of determination R² = 0.948 indicates that 94.8% of the variation in vehicle numbers can be explained by these two variables, while the remaining 5.2% is influenced by other factors outside the model. The ANOVA test produced an F-value of 54.902 with a significance of p = 0.000 (p < 0.05), confirming that the regression model is significant and valid for predicting the relationship between tourist numbers and vehicle numbers. Partially, the international tourist variable (X1) has a stronger positive effect on vehicle numbers (B = 0.363; Beta = 0.790), although its significance level is slightly above the threshold (p = 0.082). Conversely, the domestic tourist variable (X2) has a weak and insignificant effect (B = 0.068; p = 0.638). This indicates that the surge in vehicles in Bali is more closely linked to the growth of international tourists than domestic tourists. These findings highlight the importance of adaptive and sustainable transportation management to reduce traffic congestion without hindering tourism growth.